2021
DOI: 10.1080/21650020.2021.1964376
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced bicycling crashes and near misses: trends in Canadian cities

Abstract: Safety concerns are a barrier to increasing bicycling. BikeMaps.org, a tool for crowdsourcing bicycling collisions, near misses, and falls, offers rich data on local bicycling safety concerns. Our goal is to characterize dominant bicycling safety issues reported in nine Canadian cities. We analyzed 2,513 BikeMaps.org reports (522 collisions, 151 falls, 1840 near misses), and summarized the types of incidents reported, ratios of near misses to collisions by incident type and by city, and injuries resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Additionally, these findings suggest a need for a near miss monitoring or mapping system, such as BikeMaps.org, where users can log complaints to prompt action before a crash occurs. In crowdsource reports of incidents, near misses are reported at approximately 3:1, compared with crashes and near miss data ( 33 ). An even better system could be one that systematically captures near misses, as some sensor and video networks are working toward.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these findings suggest a need for a near miss monitoring or mapping system, such as BikeMaps.org, where users can log complaints to prompt action before a crash occurs. In crowdsource reports of incidents, near misses are reported at approximately 3:1, compared with crashes and near miss data ( 33 ). An even better system could be one that systematically captures near misses, as some sensor and video networks are working toward.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to collecting data on the hazard or concern, missing amenity, or incident, we ask demographic questions to determine gender, age, race, and any mobility issues on all reports ( Figure 5 ). Finally, we included a mandatory open-ended description field for the participant to provide additional details on their report as our work on BikeMaps.org has shown that these narratives provide valuable context for informing research or action ( 28 , 29 ).…”
Section: Walkrollmaporg Toolmentioning
confidence: 99%
“…Crowdsourcing data provides an opportunity to fill in data gaps related to the urban built environment ( 27 ). For example, BikeMaps.org has provided rich self-reported data that have enabled a better understanding of the contextual issues at hot spot locations ( 28 ) and trends in crash scenarios across cities ( 29 ). Another crowdsourcing app, accessnow.com, rates the accessibility of public spaces such as restaurants, trails, and shops.…”
Section: Introductionmentioning
confidence: 99%
“…Apabila insiden kecelakaan lalu lintas tidak dilaporkan, maka hal ini dapat mengurangi kewaspadaan pengguna jalan dan pengambil kebijakan tidak dapat memutuskan upaya pencegahan kecelakaan lalu lintas di wilayah tersebut (Chang et al, 2020;Sa'diyah & Enggarsasi, 2018). Masalah underreporting, dimana insiden kecelakaan lalu lintas memang terjadi tetapi belum dilaporkan, terbentuk karena adanya persepsi pelaporan kecelakaan hanya untuk jenis kecelakaan besar dan fatal dan kurangnya pengetahuan masyarakat tentang kemana harus melapor sesaat setelah terjadi kecelakaan (Laberee et al, 2021;Shinar et al, 2018;Zamzuri, 2021). Statistik kecelakaan lalu lintas saat ini hanya jumlah yang tercatat, jumlah tersebut sebenarnya dapat melebihi jumlah saat ini.…”
Section: Pelaporan Insiden Kecelakaan Secara Lengkap Dan Akuratunclassified
“…Persepsi ini perlu diubah. Penelitian sebelumnya menyimpulkan pentingnya pelaporan insiden nyaris celaka (nearmiss) dan kecelakaan non-fatal untuk menghindari jenis kecelakaan yang lebih besar terjadi di lokasi yang sama pada masa mendatang (Laberee et al, 2021;Shinar et al, 2018).…”
Section: Pelaporan Insiden Kecelakaan Secara Lengkap Dan Akuratunclassified